THE ROLE OF GENDER IN AUDIT COMITTEES ON AUDIT DELAY IN INDONESIAN FINANCIAL SECTOR COMPANIES - Khairunnisa; Defel Septian; Baiq Shelia Rara Azzahra; Vina Febrianti (Kajian Akuntansi, 2025)
Abstract . Social and cultural constructions related to gender influence perceptions regarding the roles and behavior of men and women in society, especially in carrying out their functions as members of the audit committee, because these constructions shape perceptions, expectations, and dynamics of interaction in decision-making and supervision which ultimately impact the effectiveness of the audit committee and the slowness of audit completion times. The audit committee plays a role in assisting the board of commissioners in carrying out its supervisory function through reviewing and supervising financial reports, thus influencing audit effectiveness; this effectiveness is determined not only by the formal mechanisms of the audit committee, but also by the gender composition of the audit committee, which shapes the decision-making process and the quality of supervision. This study examines the effect of the proportion of women on audit committees on audit delays in financial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. The analysis used 102 samples from a total population of 107 companies. Based on the social construction of gender theory, this study hypothesizes that female characteristics, such as greater prudence and compliance, can improve supervisory effectiveness and expedite audit completion. This study employed simple linear regression analysis using secondary data from annual reports of financial sector companies. The study results show that the proportion of women on audit committees has no impact on audit delays. This suggests that the presence of women on audit committees has not significantly contributed to timely audit completion and may currently serve only as a formality within the corporate governance structure. Nonetheless, these findings enrich the governance literature by confirming that gender influences are contextual, often dependent on organizational culture and assigned substantive roles. Practical implications emphasize the need to empower women in strategic positions to ensure their participation is meaningful and impacts the effectiveness of audits and financial reporting.